2011
DOI: 10.1103/physrevb.83.184508
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and chemical substitution effects in the local atomic structure of BaFe2As2

Abstract: The effects of K and Co substitutions and quasi-hydrostatic applied pressure (P < 9 GPa) in the local atomic structure of BaFe2As2, Ba(Fe0.937Co0.063)2As2 and Ba0.85K0.15Fe2As2 superconductors were investigated by extended x-ray absorption fine structure (EXAFS) measurements in the As K absorption edge. The As-Fe bond length is found to be slightly reduced ( 0.01Å) by both Co and K substitutions, without any observable increment in the corresponding Debye Waller factor. Also, this bond is shown to be compressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 54 publications
(97 reference statements)
8
25
1
Order By: Relevance
“…This is in very good agreement with the experimental estimate of B = 153 ± 3GPa for the collapsed tetragonal phase [10]. We also analyzed the Fe-As bond compressibility for P = 9 GPa (hydrostatic) and found κ = 3.5 × 10 −3 GPa −1 which is in excellent agreement with κ = 3.3 × 10 −3 GPa −1 obtained in an extended Xray absorption fine structure (EXAFS) experiment [26]. In Fig.…”
Section: Of Ref 5)supporting
confidence: 88%
See 2 more Smart Citations
“…This is in very good agreement with the experimental estimate of B = 153 ± 3GPa for the collapsed tetragonal phase [10]. We also analyzed the Fe-As bond compressibility for P = 9 GPa (hydrostatic) and found κ = 3.5 × 10 −3 GPa −1 which is in excellent agreement with κ = 3.3 × 10 −3 GPa −1 obtained in an extended Xray absorption fine structure (EXAFS) experiment [26]. In Fig.…”
Section: Of Ref 5)supporting
confidence: 88%
“…We expect that this overestimation affects mostly the values of P c . Comparison of our calculated Fe-As bond distances at different pressures with measured distances [26] shows good agreement. Also, available de Haas van Alphen measurements performed for CaFe 2 P 2 [25] agree well with our predicted Fermi surface shapes for CaFe 2 As 2 in the collapsed tetragonal phase.…”
Section: Of Ref 5)supporting
confidence: 64%
See 1 more Smart Citation
“…32 Recent EXAFS experiments reported that the Fe-As bonds in BaFe 2 As 2 are slightly smaller upon hydrostatic pressure, hole, and electron doping. 33 The increasing localization of the itinerant Fe d at the Fe sites claimed in this work for Ba 1−x Eu x Fe 2 As 2 is consistent with all previous experiments mentioned above and may help the understanding of the SDW phase suppression by doping in this class of materials. Now we turn our attention to the more diluted regime (x < 0.20).…”
Section: -3supporting
confidence: 77%
“…Previous EXAFS (Extended X-Ray Absorption Fine Structure) measurements on In-grown Ba122 single crystals revealed a decrease of the Fe-As distances as T SDW is suppressed by either chemical substitution (K and Co) or applied pressure 31 . In addition, DFT+DFMT calculations also predicted a decrease of the planar xy orbital contribution to the FS as the Fe-As distance is increased 15 .…”
Section: Resultsmentioning
confidence: 99%